Crimes of Bhopal and the Global Campaign for Justice - Sarangi, Satinath (Social justice, 2002)
Part of a special issue on global threats to security. The chemical disaster at the Union Carbide pesticide plant in Bhopal, India, that occurred the night of December 2–3, 1984, immediately killed over 8,000, with the death toll currently standing well over 20,000 and rising and over 120,000 survivors in desperate need of medical attention for chronic exposure-induced diseases. The legal-judicial story of Bhopal reveals explicitly the worldwide inadequacy of codes and structures to hold corporations and their senior officials accountable and the complete absence of international methods for redressing corporate crime, which have become more institutionalized, more legitimate, and more intense with the advent of globalization. Furthermore, Bhopal highlights the need and the possibility of involving the victims in defining and confronting corporate crime and illustrates the global reach of corporate crime.